Intelligent optimization for charging scheduling of electric vehicle using exponential Harris Hawks technique - Devendiran R.; Kasinathan P.; Ramachandaramurthy V.K.; Subramaniam U.; Govindarajan U.; Fernando X. (John Wiley and Sons Ltd, 2023)
Charging (batteries); Electric vehicles; Scheduling; Secondary batteries; Economic contribution; Electric Vehicles (EVs); Exponential weighted moving average; Green transportations; Intelligent optimization; Intelligent techniques; Optimization strategy; Transportation system; Vehicular ad hoc networks